An Analysis of a Fast Carrier Recovery System for TDMA - Weaver, Francis Carl (My University, 1981)
Phase-locked loops occasionally exhibit prolonged phase transients and are therefore not suitable for carrier recovery applications in time division multiple access (TDMA) systems. Instead, designers have, in several cases, used a single-tuned high Q filter in combination with an automatic frequency control. A non-linear differential equation model for such a system, called a "frequency locked loop" (FLL) is solved by computer to obtain the transient responses. The solutions obtained indicate that the FLL has fast and reliable carrier phase acquisition time compared to a phase-locked loop (PLL). Also, since the non-linear responses agree well with linear model responses, an equation based on the linear model is developed to determine worst-case acquisition time. It is shown that a limiter preceeding the single-tuned tank does not directly affect acquisition performance and will improve noise performance of the FLL. With a limiter, the FLL block diagram is equivalent to an FM feedback demodulator (FMFB) on which there is a large amount of existing literature. Using results from the literature, it is demonstrated how the FMFB will perform in the presence of Gaussian noise. Finally, a design procedure is recommended which takes into account the tradeoff between noise performance and acquisition/tracking ability and attempts to minimize the acquisition time for a given level of Gaussian noise.
Keywords: Electrical and Electronics; Electrical and Electronics